Prevalence and factors associated with hypertension: A cross-sectional study among the elderly population in Pokhara metropolitan city. - Mishra,Rima (2020)
ABSTRACT: Background: Hypertension (HTN) is rapidly emerging as a public health problem among elderly population in developing countries. Hypertension is a condition in which the blood vessels have persistently raised pressure where the systolic blood pressure is ≥ 140 mm Hg and/or diastolic blood pressure is ≥ 90 mm Hg. The objective of this study was to assess the prevalence of hypertension and its associated factors among the elderly population in Pokhara Metropolitan. Methodology: A cross-sectional analytical study design was carried out to assess hypertension among 323 elderly population in Pokhara Metropolitan from October 2019 to March 2020. Quota sampling was used to collect the samples. Face to face interview was done for data collection and anthropometric measurements, and semi structured standard STEPS questionnaires were used as data collection tools. Data were entered in Epi DATA [Version 3.1] and analyzed using SPSS [Version 20] as per data analysis plan. Results: Prevalence of hypertension was reported among 34.4 percent (Male 39.3%, Female 29%) elderly population in Pokhara Metropolitan. The higher proportion of hypertensive cases were in age group 60-69 years (36%). The prevalence of hypertension was significantly associated with ethnicity (OR= 1.74, CI: 1.07-2.83), current alcohol intake (OR= 2.56, CI: 1.30-5.05) and mental stress (OR= 2.25, CI: 1.19- 4.28). Conclusion: More than one third of the elderly population had hypertension. Ethnicity, current alcohol intake and mental stress are found to be factors associated with hypertension. Periodic screening for early detection of hypertension and implementing health promotion interventions to encourage behavior change among elderly population may promote healthy ageing. Keywords: Hypertension, prevalence, risk factors, elderly population, Nepal